Revealing The Meaning Of Bai ’And Tijarah In Al-Qur'an (Interpretation Of Economic Verses) - Farid Ikhwanuddin; Roni Hidayat (Jurnal Ekonomi dan Perbankan Syariah, 2019)
One form of economic activity carried out by humans is trade. It can be said that trade is the oldest activity carried out by humans in fulfilling their daily needs. Mecca at that time was a major international trade and shopping center, and Islam was born in the militia of Mecca trade. Once the Islamic attachment to trading activities, many narratives of the verses of the Qur'an seemed to be directed at the merchants. Qur'an was first addressed to the merchants reflected in the language and ideas". More specifically, disclosure of trade in the Qur'an can be found through lafadz bai 'and tijarah. In the following article a thematic review of lafadz bai 'and tijarah and its derivatives is presented, which is analyzed using the Makkiyyah and Madaniyyah studied tematic. In the Qur'an the verses which reveal lafaz bai 'in various variations are contained in eleven verses scattered in different letters, while the Disclosure of lafadz tijarah in the verses of the Qur'an is mentioned eight times in seven letters. The form of disclosure of the Lafadz is entirely the same in the form of mashdar (تجارة).